ANALISA BEBAN KERJA DAN PENGEMBANGAN PERSAMAAN PREDIKSI KONSUMSI OKSIGEN PADA MAHASISWA PEKERJA INDUSTRI (STUDI KASUS MAHASISWA TEKNIK INDUSTRI UNIVERSITAS RIAU KEPULAUAN) - Siboro, Benedikta Anna Haulian; Afma, Vera Methalina (SENATIK STT Adisutjipto, 2016)
Majority of Industrial Engineering student at Riau Island Univeristy - Batam are workers who mostly worked in the electronics industry and shipbuilding with different kind of work.In this research, the variables to be studied is work load  which is done on whether the worker was within normal limits and develop VO2 consumption equation for each of these jobs by doing research using bike ergonometer and doing manual handling. The data obtained from  recording of the heart rate, as well as student worker health data is later processed and searched the prediction equation using statistical methods such as the independence of the error test, test multicollinearity between independent variables and stepwise methodThe results showed from 240 students, 80% of student work on the electronics manufacturing and the rest in other areas and does not work. It is also at submaximal measurements using Ergocycle bike show in the 8th minute decrease in heart rate and so is the removal of objects in a decrease in heart rate in the 10th minute and classified in extreme jobs. There was also a correlation between VO2 maximum height and heart rate in order to get the equation VO2 = -0054 +0015 High HR + 8939 Keywords : consumption VO2, bike Ergocycle, workload, type of work